What is Sumak Kawsay? A Qualitative Study in the Ecuadorian Amazon. (May 2021) - Coral-Guerrero, Carmen Amelia; García-Quero, Fernando; Guardiola, Jorge
A qualitative study of the main characteristics of sumak kawsay ( buen vivir, living well/good life) in the Ecuadorian Amazon shows that it has four constitutive elements of which a multitude of interpretations coexist: an indigenous and nature-focused worldview, community, an economy based on solidarity, and ancestral knowledge. Understandings of sumak kawsay are rooted in the practices and beliefs of the communities interviewed rather than in theoretical constructions of idyllic community forms, and in this connection differences can be observed between the academic "indigenist" view of it and local discourses. Una aproximación cualitativa a las características principales del sumak kawsay ( buen vivir, living well/good life) en la Amazonía ecuatoriana muestran la existencia de cuatro elementos constitutivos del sumak kawsay en los que colindan multitud de interpretaciones: cosmovisión indígena y naturaleza, comunidad, economía solidaria, y conocimiento ancestral. Las comprensiones del sumak kawsay enraízan con prácticas y creencias de las personas y no con construcciones teóricas de formas comunitarias idílicas, y al respecto, apreciamos diferencias entre la visión académica "indigenista" del sumak kawsay y los discursos locales.